2023
DOI: 10.1002/mdc3.13813
|View full text |Cite
|
Sign up to set email alerts
|

Can Patients with Wilson's Disease Develop Copper Deficiency?

Abstract: BackgroundWilson's disease (WD) is a rare genetic condition characterized by a copper overload in organs secondary to mutation in ATP7B gene. Lifelong decoppering treatments are the keystone of the treatment but must be regularly adapted to obtain a correct copper balance and could lead to copper deficiency (CD).ObjectivesStudy the characteristics of CD in WD patients.MethodsCD cases from our cohort of 338 WD patients have been investigated. CD was defined by the association of serum copper, exchangeable coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Patients with liver and kidney insufficiency are unable to transport the ingested copper ions in the body in time, resulting in the deposition of copper ions in the body. In addition, some inherited or acquired disorders can cause copper ion homeostasis [ 33 , 34 ]. Since copper is essential for the proper functioning of cells, and copper overload is cytotoxic, the amount and distribution of available copper in the body must be tightly controlled to minimize the potential toxicity of copper while meeting metabolic needs.…”
Section: Copper Ionsmentioning
confidence: 99%
“…Patients with liver and kidney insufficiency are unable to transport the ingested copper ions in the body in time, resulting in the deposition of copper ions in the body. In addition, some inherited or acquired disorders can cause copper ion homeostasis [ 33 , 34 ]. Since copper is essential for the proper functioning of cells, and copper overload is cytotoxic, the amount and distribution of available copper in the body must be tightly controlled to minimize the potential toxicity of copper while meeting metabolic needs.…”
Section: Copper Ionsmentioning
confidence: 99%
“…The study of Chevalier et al 1 also raises the question of how to monitor the status of body deposits of copper and those of zinc in WD patients on therapy. It is widely accepted that during zinc therapy, the levels of zincuria must be higher than 2000 μg (61 μmol)/24 hours, whereas the cupruria must be lower than 75 μg (1.2 μmol)/24 hours 4,5 .…”
mentioning
confidence: 99%
“…In recent American Association for the Study of Liver Diseases guidelines, it is reported that the development of cytopenias, an increase in serum ferritin, and/or disproportionately low 24‐hour urinary copper excretion (<100 μg/24 hour for chelation therapy; <20 μg/24 hour [<0.3 μmol/24 hour] for zinc therapy) may be indicative of overtreatment 4 . Information on the behavior of ferritin is lacking in the Chevalier et al's 1 study and in the literature review. This study once again underlines the role of free copper determination in monitoring a WD patient under therapy, but as is well known, despite the initial encouraging studies, it is not a test for routine use 4 …”
mentioning
confidence: 99%
See 2 more Smart Citations